Comprehending the role of homeopathic preparations of Rauwolfia serpentina on oxidative stress parameters of cardiac tissue of DOCA-salt induced hypertensive male rats: An experimental approach - Sandeep Kumar; Gagan Bihari Nityananda Chainy; Jagneshwar Dandapat; Akshaya Kumar Hati; Laxmikanta Nanda (Elsevier, 2021)
Background: Oxidative stress has been associated in various pathophysiology of heart including hypertension, a global concern. The present work reports the effect of oral administration of different potencies of homeopathic preparations of R. serpentina (Q, 30c and 6c) on oxidative stress parameters of the ventricular cardiac tissue of hypertensive male rats. Method: Hypertension was induced in unilaterally nephrectomized male rats by injecting DOCA (25 mg/kg BW) twice in a week and 1% NaCl in drinking water. Hypertensive rats were treated with different potencies of R. serpentina (Q, 30c and 6c) orally twice a day for 30 days. Oxidative stress parameters (lipid peroxidation and protein carbonyl content) and activities of enzymatic antioxidants, superoxide dismutase, catalase, glutathione erpentine, glutathione reductase and glutathione S-transferase were measured in cardiac tissue. Transcript and translate level of SOD1, SOD2, CAT and transcript level of GPx and GR were analysed in cardiac tissue. Results: The enhanced oxidative stress parameters in post mitochondrial (PMF) and mitochondrial fractions (MF) of ventricular tissue were reduced in response to Q, 30c and 6c of R. serpentina. Superoxide dismutase activity in PMF of ventricular tissue was elevated in response to Q of R. serpentina. The mRNA and translated products of SOD1 were elevated in response to Q and 30c of R. serpentina. Translated products of SOD2 were increased in PMF in response to Q and 30c treatment. A reduction in its level in MF was recorded in response to 30c. Catalase exhibits a dual response i.e. its activity was upregulated and downregulated, respectively, in the PMF and MF in response to drug treatment. Although glutathione peroxidase activity in the PMF of the ventricular tissue was decreased in response to 30c and 6c potencies, its activity in MF was elevated in response to 6c. Conclusions: Results suggest that homeopathic medicine R. serpentina reduces hypertension and associated oxidative stress in the cardiac tissue by modulating the antioxidant defence system.